Congenital Chylothorax: Case Report - Tolunay, Egemen; Varlı, Bulut; Tülek, Fırat; Pabuçcu, Emre; Çetinkaya, Şerife Esra; Kahraman, Korhan; Koç, Acar (Gynecology Obstetrics & Reproductive Medicine, 2013)
We present a case of fetal chylothorax while discussing about its management and outcomes. Fetal pleural effusion causes pulmonary hypoplasia of the lungs. Patient with 31 weeks of gestation has detected to have a fetal pleural effusion by routine ultrasonographic imaging. Fetal echocardiography was unable to demonstrate a cardiac pathology. Fetal thoracentesis revealed lymphocyte predominance and chylothorax was diagnosed. Chromosome analysis, metabolic screening and TORCH screening were normal. After the application of antenatal steroids, a caesarean section was performed at 34th gestational week. The newborn was taken to neonatal intensive care unit. After treatment with medium-and short-chain fatty acids, octreotid, and pleural drainage newborn is discharged from the hospital well two months later. Chylothorax is one of the rare causes of respiratory distress in term neonates and most commonly occurs due to hydrops fetalis and perinatal infections. Rarely, congenital malformations of the thoracic duct and variational changes of embryonic lymphatic network were reported after autopsy. Some cases of chylothorax are found to be associated with Turner, Down and Noonan syndromes. Genetic analysis and infection screening should be considered to reveal the etiology. Usually chylothorax has a good prognosis. However prematurity, hydrops fetalis and degree of pulmonary hypoplasia are the factors determining the mortality rate. As a result, chylothorax should be included in the differential diagnosis of pleural effusion in the neonates, and thoracentesis should be made for early diagnosis. Appropriate and effective treatment of patients with chylothorax may contribute to the prognosis and neonatal survival.